Flow dynamics and sediment transport in vegetated rivers: A review - Huai, Wen-xin; Li, Shuolin; Katul, Gabriel G.; Liu, Meng-yang; Yang, Zhong-hua (Journal of hydrodynamics. Series B, 2021)
The significance of riparian vegetation on river flow and material transport is not in dispute. Conveyance laws, sediment erosion and deposition, and element cycling must all be adjusted from their canonical rough-wall boundary layer to accommodate the presence of aquatic plants. In turn, the growth and colonization of riparian vegetation are affected by fluvial processes and river morphology on longer time scales. These interactions and feedbacks at multiple time scales are now drawing significant attention within the research community given their relevance to river restoration. For this reason, a review summarizing methods, general laws, qualitative cognition, and quantitative models regarding the interplay between aquatic plants, flow dynamics, and sediment transport in vegetated rivers is in order. Shortcomings, pitfalls, knowledge gaps, and daunting challenges to the current state of knowledge are also covered. As a multidisciplinary research topic, a future research agenda and opportunities pertinent to river management and enhancement of ecosystem services are also highlighted.